Theater of Triumph and Transgression: Religious Discourse on Hospitality/Hostility in the Viral Communication during the Pandemic - Epafras, Leonard Chrysostomos; Kaunang, Hendrikus Paulus; Tarigan, Jekonia; Rafsanjani, David Akbar Hasyemi (Al-Albab, 2023)
The present article is the outcome of the research project on religious discourse in social media (socmed) during the COVID-19 pandemic. The research focuses on the concept of hospitality and hostility, through which a welcoming, along with hostile and unfriendly attitude are displayed by netizens toward other people, to understand the nature of social relationships over digital platforms. The research employs Social Network Analysis (SNA) and Social Media Analysis to explore and visualize viral communication on Twitter, Facebook, and Instagram. The framework is viral communication as condensed sequences of actions revolving around controversial topics. Several topics under scrutiny, among others, are klepon Islami, Hagia Sophia, and Pope Francis’ controversies. Jacques Derrida mainly informs the discourse of hospitality/hostility. The result demonstrated the sporadic vulnerability of traditional understanding of hospitality. It appeared in the presence of information arbiters as communication actors, taking the middle position and mediating controversial topics. The employment of SNA in dealing with interpersonal virtues in social media is promising, as it demonstrates its mechanism and making in a specific communication context. It allows for a deeper understanding and exploration of the theory of mediatization.